Podlaga za izdelavo usmeritev pri gospodarjenju z navadno smreko v Sloveniji - Krajnc, Luka (Gozdarski vestnik, 2022)
In our article, we present the foundation for the preparation of the guidelines for Norway spruce management in Slovenia. We performed several separate analyses following the same goal: to prepare professionally founded and data-supported guidelines for Norway spruce management in Slovenia in the future decades. Thus, in this article, we combined the measurement results of the national forest inventory, spruce increment analysis, species diversity analyses, and overview of the drafts of the forest management regions plans. This article aims to present the results of the four separate data analysis complexes representing the foundation for the preparation of the guidelines in the Norway spruce management, published in the next article.
Keywords: climatic changes; gospodarjenje; management; navadna smreka; Norway spruce; podnebne spremembe